2021
DOI: 10.1016/j.scitotenv.2020.143118
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in radiometrically dated sediment cores from English lakes show polybrominated diphenyl ethers correlate with brominated but not mixed bromo/chloro dioxins and furans

Abstract: This paper reports concentrations between ~1950 and present, of polybrominated diphenyl ethers (PBDEs) and polybrominated dibenzo-p-dioxins and furans (PBDD/Fs), in radiometrically-dated sediment cores from three English lakes. Mixed bromo/chloro dibenzo-p-dioxins and furans (PXDD/Fs) were measured in two of the same lakes. Concentrations of PXDD/Fs decreased over time to the present. To our knowledge, this is the first report of temporal trends of PXDD/Fs in the environment. In contrast, concentrations of PBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The most effective method to reduce bioaccumulative PBDE congener concentrations was to use microorganisms combined with source control, which was almost as effective as dredging for the rest of the congeners (Karakas et al, 2020). Peters et al (2021) noted a positive correlation between the occurrence of PBDEs and PBDFs and suggested that an increased use of PBDEs contributed to environmental contamination with PBDFs which can be formed from PBDEs (see Section 1. 3.3.1) . An examination of PBDF homologue patterns indicated that emissions from combustion activities are likely also important sources of contamination.…”
Section: Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective method to reduce bioaccumulative PBDE congener concentrations was to use microorganisms combined with source control, which was almost as effective as dredging for the rest of the congeners (Karakas et al, 2020). Peters et al (2021) noted a positive correlation between the occurrence of PBDEs and PBDFs and suggested that an increased use of PBDEs contributed to environmental contamination with PBDFs which can be formed from PBDEs (see Section 1. 3.3.1) . An examination of PBDF homologue patterns indicated that emissions from combustion activities are likely also important sources of contamination.…”
Section: Sedimentmentioning
confidence: 99%
“…Peters et al. ( 2021 ) noted a positive correlation between the occurrence of PBDEs and PBDFs and suggested that an increased use of PBDEs contributed to environmental contamination with PBDFs which can be formed from PBDEs (see Section 1.3.3.1 ). An examination of PBDF homologue patterns indicated that emissions from combustion activities are likely also important sources of contamination.…”
Section: Introductionmentioning
confidence: 99%